Fuentes que determinan la imagen de un destino turístico según los trabajadores de hoteles y hostales de tres estrellas, ciudad de Iquitos, 2019 - Machuca Alvis, Rosa Ines (2019)
The purpose of the thesis is to obtain the sources that determine a tourist destination according to the opinion of the workers about visitors of the hotels and three-star hostels of the Iquitos city this year. The problem arises from the need to understand and know the way of choosing tourist destinations based on the model Gartner (1997) of the publication "Image and sustainable tourism systems" and that was adapted for the study. The methodology used is that of an applicative, quantitative study with a descriptive transectional design in which they obtain data in a single moment. The population is the workers of hotels and three-star hostels, the sample unit is the worker and the Sample is for the convenience of 34 workers of the establishments. The instrument was submitted to the reliability index: Cronbach's alpha, which resulted in: 0.832 of its content, which has 21 items, consequently the data collection instrument is highly reliable. We arrived at conclusions that the sources induced Open I (indicator 2), the autonomous sources (indicator 1 and 2), the organic sources requested (indicator 1 and 2) and the organic sources (indicator 1, 2, 3 and 4) in its totality, were the sources that determine the travel destination of tourists in the locality. Thus, based on these results, these indicators stated in the statistical hypothesis were accepted.